The Relationship Between E-Cigarette Use and Propylene Glycol Content in Males Aged 17–25 Years with the FEV1 and FVC Ratios in Relation to COPD in South Jakarta and its Analysis from an Islamic Perspective - Fatiana Maharani Lubis; Teguh Yuliadi; Irwandi M. Zen; Fitri Fitri (Jurnal Indonesia Sosial Sains, 2026)
E-cigarettes are widely used among young adults, with propylene glycol (PG) as a common component. While PG has been associated with potential respiratory risks, its impact on lung function—particularly the FEV1/FVC ratio—remains unclear in young male populations. This study also examines the Islamic perspective on e-cigarette use, considering health preservation (hifz al-nafs) and harm avoidance (darar). To investigate the relationship between e-cigarette use and PG exposure on lung function, and to analyze the findings from an Islamic ethical standpoint, a cross-sectional study was conducted with 40 male e-cigarette users aged 17–25. Data were collected through spirometry to measure FEV1/FVC ratios, along with structured interviews on e-cigarette use habits, respiratory symptoms, and demographic variables. Statistical analysis was performed to assess correlations. All participants had normal FEV1/FVC ratios (>75%), with no significant association found between e-cigarette use, duration, or PG exposure and impaired lung function. However, 47.5% reported subjective respiratory symptoms, and 7.5% noted libido changes. BMI varied widely, with 72.5% of respondents classified as overweight or obese. E-cigarette use in young males was not associated with measurable declines in lung function based on FEV1/FVC ratios, despite reported respiratory complaints. Long-term effects remain uncertain. From an Islamic perspective, e-cigarette use is debated; most scholars consider it makruh (discouraged) due to potential harm and wasteful expenditure, though explicit religious rulings remain contextual